Towards optimal search: a modified secant method for efficient search in a big database - M. Nomani, Kabir; Ali, Jahan; Alginahi, Yasser M.; Benseghir, Hocine (Universiti Malaysia Pahang, 2018)
Search techniques are integral part for text authentication and plagiarism checks. In this work, our aim is to develop an efficient search algorithm for Arabic texts in a big database. The database contains the authentic source of information where information is ordered; thus the efficient algorithm can be used for searching the texts. Our search algorithm uses a quasi-Newton method -Secant method instead of traditional binary search. The secant method has much faster convergence property than the binary search and hence the algorithm can find the specific texts in a shorter time period.